Kinematic Analysis of Performance of World Class Javelin Thrower - Biswajit Sharma; Kishore Mukhopadhyay (Inspiree, 2022)
The purpose of the study. Charles Darwin’s concept of the struggle for existence is now converted into a struggle for excellence. The ancient spear and hunting in now converted popular athletic sporting events in the form of javelin throw. Science plays a major role in maximizing the javelin throw's horizontal distance. Tremendous research indicates the various kinematic parameters and their role in better performance. The present analytical study discusses the trends of research in javelin performance and their successful implementation in the actual sporting field. The purpose of the study is to compare the different research findings for better javelin performance on kinematic parameters and analysis of biomechanical parameters such as height, weight, BMI, and performance of the last ten  Olympic gold medals holders both male and female javelin throwers.